Benefit of plasma exchange with albumin replacement on individual items of the quality of life‐Alzheimer’s disease score - Stewart, Walter F; Lipton, Richard B.; Gomez‐Ulloa, David; Runken, M Chris; Grifols, Carlota; Iaconangelo, Charlie; Serrano, Daniel (Alzheimer's & dementia, 2023)
Background Alzheimer Management By Albumin Replacement (AMBAR) is a multicenter, randomized, placebo‐controlled, Phase IIb/III clinical trial that evaluated the efficacy and safety of Plasma Exchange with Albumin replacement (PE‐A) in patients with mild‐to‐moderate Alzheimer’s disease (Boada et al., Alzheimers Dement. 2020). PE‐A has demonstrated an overall benefit in quality of life as measured by the Quality of Life‐Alzheimer’s disease (QoL‐AD) score (Boada et al., Alzheimers Dement. 2021). We evaluated PE‐A treatment benefit for each of 13 individual patient‐rated QoL‐AD items. Method A cumulative logistic mixed model was applied on the Full Analysis Set (FAS) population. The odds that a patient receiving PE‐A would have a more favorable response (i.e., higher item score) than a similar subject receiving placebo was estimated at final visit for each QoL‐AD item. Age, baseline MMSE score, and baseline individual QoL‐AD item responses were included as covariates. Result The FAS included 76 placebo patients and 229 PE‐A‐treated patients. A significant PE‐A treatment effect vs. placebo at final visit was observed for QoL‐AD item 4: Living situation (“How do you feel about the place you live now?“) [Odds Ratio (OR) = 3.92 (95% CI: 1.38‐11.12), p = 0.010] and for QoL‐AD item 13: Life as a whole (“When you think about your life as a whole, everything together, how do you feel about your life?”) [OR = 3.80 (95% CI: 1.32‐10.91), p = 0.013]. Conclusion The analysis demonstrated that when compared to patients on placebo, patients receiving PE‐A were more likely to have a favorable response for the QoL‐AD items “Living situation” and “Life as a whole”, suggesting that the reported benefit of PE‐A vs. placebo on the full QoL‐AD score is also observed in these individual QoL‐AD items.